Evidence of a Pivotal Role for the Distal Part of the Complement Cascade in the Diurnal Release of Hematopoietic Stem Cells into Peripheral Blood. Issue 2 (February 2016) - Borkowska, Sylwia; Suszynska, Malwina; Ratajczak, Janina; Ratajczak, Mariusz Z.
We found that diurnal activation of the three evolutionarily ancient proteolytic cascades in peripheral blood (PB), namely, the complement, coagulation, and fibrinolytic cascades, late at night or in the early morning hours, precedes the diurnal release of hematopoietic stem/progenitor cells (HSPCs) from bone marrow (BM) into PB in wild-type mice. Moreover, activation of the distal part of the complement cascade (ComC), involving cleavage of the fifth component (C5), seems to play a crucial role in pharmacological mobilization of HSPCs. In order to shed more light on the role of diurnal rhythms in the egress of HSPCs, we studied diurnal changes in the number of circulating HSPCs in C5-deficient mice and did not observe diurnal changes in the number of these cells circulating in PB in C5 -/- animals. Based on this finding, we conclude that activation of the distal part of the ComC, C5 cleavage, and release of C5a and desArgC5a are required in executing the diurnal release of HSPCs from BM into PB. Moreover, the fact that C5 -/- mice still displayed normal activation of the coagulation and fibrinolytic cascades indicates that, of all the proteolytic cascades, the ComC is the dominant player regulating diurnal egress of HSPCs.